Collaborative Learning through Inside Outside Circle (IOC)- Post to Post Game in 21st Century Mufradat Learning - Alifia Azizah; Tatang Tatang; Nalahuddin Saleh; Mia Nurmala (Edumaspul: Jurnal Pendidikan, 2024)
One of the cooperative learning models is the Inside Outside Circle (IOC) learning method. The IOC-Post to Post Game method combines elements of cooperative learning with the Post to Post Game. In the IOC-Post to Post Game students work together in teams by exchanging information and collaborating to complete a given task or order. 21st-century learning requires students to have 21st-century skills to face future challenges. Based on that, a learning method is needed to achieve learning goals and train essential skills for 21st-century learners, including in Arabic language learning. In Arabic language learning, vocabulary mastery is the main foundation that must be possessed. A study conducted at MI Nurul Huda in the third grade aims to determine whether there is an influence of collaborative learning methods through IOC-Post to Post Game on students' mastery of vocabulary in the third grade. This study used a quantitative approach, namely a Quasi-Experiment with Nonequivalent Control Group Design. The data collection techniques used were tests in the form of pre-tests and post-tests and non-tests in the form of interviews and documentation. The findings of this study are that the collaborative learning method IOC-Post to Post Game has an effect on students' understanding of vocabulary with a moderate level of effectiveness, with an N-Gain Score of 0.320, and the collaborative learning method IOC-Post to Post Game has a positive impact on students' activity and social skills.